131k views
2 votes
Which could you use to prove triangle AED is congruent to triangle CEB?

Which could you use to prove triangle AED is congruent to triangle CEB?-example-1
User NullUser
by
5.3k points

1 Answer

3 votes

Answer:

Option (C)

Explanation:

Given:

In right triangles ΔAED and CEB,

m∠AED = m∠CEB = 90°

DE ≅ BE

AD ≅ BC

To prove:

ΔAED ≅ ΔCEB

Statements Reasons

1). m∠AED = m∠BC = 90° 1). Given

2). DE = BE 2). Given

3). AD = BC 3). Given

4). ΔAED ≅ ΔCEB 4). By HL theorem of congruence

Option (C) is the answer.

User Darko Romanov
by
5.7k points